DEVELOPMENT OF ADOBE FLASH MULTIMEDIA-BASED INTERACTIVE LEARNING MEDIA ON THE TYPE OF EMPLOYMENT IN SOCIAL SCIENCE LEARNING SUBJECTS AT GRADE IV SD - Dea Risti Andiani; M. Taufik; Zerri Rahman Hakim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the development of adobe flash multimedia-based interactive media in social science learning subjects, especially on the learning material of the employment types at grade IV. The research method used by the author is Research and Development (R&D), which consists of the stages of problem analysis, data collection, product design, product design validation, product revision, and product testing. To test the feasibility of this learning video, the validation test was applied by media and material experts. The product was tested with the research subject, which involved 20 fourth-grade students of SDN Bama 3. Based on the validation results regarding interactive learning media based on adobe flash multimedia the validation from media experts was categorized as